Diagnostic and therapeutic value of P2Y12R in epilepsy - Chen, Xiang; Wang, Qi; Yang, Jie; Zhang, Li; Liu, Ting-Ting; Liu, Jun; Deng, Bin-Lu; Liu, Jie (Frontiers in Pharmacology, 2023)
There lacks biomarkers in current epilepsy diagnosis, and epilepsy is thus exposed to inadequate treatment, making it necessarily important to conduct search on new biomarkers and drug targets. The P2Y12 receptor is primarily expressed on microglia in the central nervous system, and acts as intrinsic immune cells in the CNS mediating neuroinflammation. In previous studies, P2Y12R in epilepsy has been found capable of controlling neuroinflammation and regulating neurogenesis as well as immature neuronal projections, and its expression is altered. P2Y12R is involved in microglia inhibition of neuronal activity and timely termination of seizures in acute seizures. In status epilepticus, the failure of P2Y12R in the process of "brake buffering" may not terminate the neuronal hyperexcitability timely. In chronic epilepsy, neuroinflammation causes seizures, which can in turn induce neuroinflammation, while on the other hand, neuroinflammation leads to neurogenesis, thereby causing abnormal neuronal discharges that give rise to seizures. In this case, targeting P2Y12R may be a novel strategy for the treatment of epilepsy. The detection of P2Y12R and its expression changes can contribute to the diagnosis of epilepsy. Meanwhile, the P2Y12R single-nucleotide polymorphism is associated with epilepsy susceptibility and endowed with the potential to individualize epilepsy diagnosis. To this end, functions of P2Y12R in the central nervous system were hereby reviewed, the effects of P2Y12R in epilepsy were explored, and the potential of P2Y12R in the diagnosis and treatment of epilepsy was further demonstrated.